2022
DOI: 10.1097/iae.0000000000003450
|View full text |Cite
|
Sign up to set email alerts
|

Panretinal Photocoagulation Versus Intravitreal Bevacizumab Versus a Proposed Modified Combination Therapy for Treatment of Proliferative Diabetic Retinopathy

Abstract: Purpose: To compare safety and therapeutic effect of three treatment protocols on patients with naive proliferative diabetic retinopathy.Methods: A total of 207 eyes with proliferative diabetic retinopathy were randomly divided into three groups: full panretinal photocoagulation group; intravitreal bevacizumab (IVB) group with four monthly IVB injections; and modified combination group with two bimonthly IVB injections and a modified laser therapy. The best-corrected visual acuity and area of neovascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…31 This study included 207 eyes and assessed visual acuity and areas of leakage from neovascularization (based on fluorescein angiography) at 1 year. 31 The combination therapy arm included a modified laser treatment applied only to the retina anterior to the equator. Final analyses showed no statistically significant difference in visual acuity between the 3 treatment arms (P = 0.77) and a smaller area of leakage in the combination treatment arm (P = 0.006).…”
Section: Anti-vascular Endothelial Growth Factormentioning
confidence: 99%
See 3 more Smart Citations
“…31 This study included 207 eyes and assessed visual acuity and areas of leakage from neovascularization (based on fluorescein angiography) at 1 year. 31 The combination therapy arm included a modified laser treatment applied only to the retina anterior to the equator. Final analyses showed no statistically significant difference in visual acuity between the 3 treatment arms (P = 0.77) and a smaller area of leakage in the combination treatment arm (P = 0.006).…”
Section: Anti-vascular Endothelial Growth Factormentioning
confidence: 99%
“…Final analyses showed no statistically significant difference in visual acuity between the 3 treatment arms (P = 0.77) and a smaller area of leakage in the combination treatment arm (P = 0.006). 31 A smaller study with 40 eyes investigated the efficacy of conventional ETDRS PRP + IVT ranibizumab versus PASCAL PRP + IVT ranibizumab versus IVT ranibizumab alone for PDR. Outcomes measured included visual acuity, macular thickness, and retinal neovascularization using fluorescein angiography testing at 48 weeks.…”
Section: Anti-vascular Endothelial Growth Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies, such as RESTORE (65), VISTA and VIVID (66) study have shown that the emergence of anti-VEGF therapy led to significant clinical improvements compared to laser therapy alone. Besides, a recent randomized clinical trial observed that combination of intravitreal bevacizumab injections and laser photocoagulation was more effective in preventing neovascularization and ameliorating visual field than pan-retinal photocoagulation (PRP) or bevacizumab alone in PDR patients (67). The combined protocol reduced the adverse effects of full PRP and need fewer injections and visits, suggesting that for some high-risk patients, anti-VEGF combined with PRP therapy may be more helpful in delaying the progression and improving the adherence of injections in DR.…”
Section: Anti-vegf Therapymentioning
confidence: 99%